The Difference in the Glucose Levels of Rice Cooked with Rice Cooker and Steaming - Linda Juwita (JURNAL KESEHATAN PRIMER, 2019)
Background: How to process rice will cause changes in rice content and cause differences in glucose levels in rice. Rice is a daily food for Indonesian people. Carbohydrates contained in rice will be converted into glucose. Sugar levels in food affect the glycemic index High glycemic index is a factor causing hyperglycemia. The purpose of this study was whether there were differences in glucose levels in rice after being cooked by the rice cooker method and by the steaming method. Methods: Glucose levels were determined by the dinitrosalicylic acid Method: the spectrophotometric-colorimetric method using cooked rice with various rice cooker and steaming methods. Each sample was repeated three times. Data were tested using the Statistical test with the Mann Whitney test. B p> 0.05 which means there is no significant difference in glucose levels in rice after cooking with the rice cooker method and with the steaming method. Conclusion: Glucose level of rice is influenced by several factors, namely the quality of the rice from the rice processing, the quality of the type of rice, the measurement temperature.